An Exploration of Comprehensive Student Support Systems in Technical Vocational Education and Training Colleges for Students with Disability. Issue 2 (1st February 2023) - Munyaradzi, Muchineripi; Arko-Achemfuor, Akwasi; Quan-Baffour, Kofi
ABSTRACT: There has been an increase in enrollments for students with disabilities in the post-school education sector in South Africa of late. This category of students encounters numerous challenges during their time of study at institutions of learning. It is imperative therefore for tertiary institutions to establish a learning environment that addresses challenges faced by students with disabilities. The public Technical, Vocational Education and Training (TVET) sector in South Africa offers student support services to the enrolled students including this cohort. The paper utilized the qualitative approach and the interpretivist paradigm to derive profound understanding of student support systems in TVET colleges for students with disability. This paper is a case study which focuses on student support systems for students with disabilities. The barriers to the effective utilization of student support services and strategies of mitigating challenges experienced by students with disabilities are explored in this paper. The case study involved student support staff (10) and students (36) from two public TVET colleges in the KwaZulu-Natal province of South Africa on student support systems for students with disabilities. It emerged from the study that students with disability experience challenges that interfere with their academic journey and noted further that the existing student support systems in the TVET sector does not adequately address the varying needs of students with disability.